Policy responses to the sexual and reproductive health of queer youth in the global south: a systematic review - Moore, Sarah-Ann (Rhodes University, Faculty of Humanities, Department of Psychology, 2018)
Concerns surrounding youth sexual and reproduction health (SRH) are deeply embedded within systems of heteronormativity and ciscentrism. Resultantly, youth SRH is filtered through a lens of heterosexual and cisgender experience, rendering invisible the SRH needs of queer youth. Importantly, a failure to recognise queer experiences of SRH has implications for normative subject positions, which enjoy stronger institutional support and constitute legitimate ways of being. As such, the failure to recognise queer youth as health care subjects within policy has far reaching consequences for their sexual and reproductive health. Within this research, a sexual and reproductive justice (SRJ) framework is adopted as a backdrop for exploring policy documents related to youth SRH within selected global South countries in Africa, Asia, and the Caribbean. The final data set comprises of 1035 policy excerpts extracted from 152 policies across these three regions. Research takes the form of a systematic review utilising a deductive framing and positioning thematic analysis. Analysis identifies framings of youth SRH and explores the subject positions assigned to queer youth in relation to these identified framings, with the understanding that the manner in which youth SRH concerns are framed and queer youth are positioned within policies provides an important foundation for the implementation of SRH-related policy. Findings demonstrate that policy responses to youth SRH are most often framed in terms of a public health approach. As a result, dominant understandings of youth SRH serve to reduce youth sexuality to notions of infections and impact, which may speak to an overreliance on biomedical and population-level health models. Themes emerging within human rights framings demonstrate a presumption that rights are equally afforded to, and freely exercised by, all individuals once legally secured, failing to engage with the creation of enabling conditions to realise these rights. Although context and culture framings were by no means exhaustive examples of SRJ, they provide an interesting insight into how such SRJ concerns might be integrated into policy. Importantly, policy responses demonstrate a general pattern hypervisibility of men who have sex with men (MSM) standing in marked contrast to the invisibility of queer youth and other adult queer populations. Within policy extracts, both youth and MSM"Ÿ are positioned as particularly prone to poor SRH outcomes. By virtue of their inclusion within both populations, queer youth may be considered as especially at risk for, or vulnerable to, such outcomes. Relatedly, these populations (and by extension queer youth) are positioned as in need of correction, containment, and/or protection by those occupying gatekeeping"Ÿ positions (e.g. health care providers). The positioning of MSM"Ÿ solely within the context of HIV/AIDS serves to link same-sex sexualities (and at times gender non-conformity) with harmful consequences, suggesting that the positioning of queer youth could similarly serve to conflate their SRH needs with concerns around HIV/AIDS. Many of the subject positions deployed in policies serve to deny the potential for youth and MSM"Ÿ agency, strength, and resilience. Thus, queer youth subjects are unlikely to be positioned as empowered, autonomous, and agentic. Across both framing and positioning themes, a number of key shortcomings were observed. For the most part, policy responses fail to acknowledge the influence of social, economic, political, and cultural forces that may serve to hinder SRH outcomes according to particular contexts and the intersection of multiple and varied social identities. By obscuring these broader contextual factors and power relations, policy responses may serve to hold individual youth responsible for poor SRH outcomes. In failing to engage with the potential for diversity within youth populations, these populations are largely homogenised. Finally, the need for the creation of an enabling environment in order to secure sexual and reproductive health is largely unacknowledged within policy responses.
Keywords: Sexual minorities -- Africa; Sexual minorities -- Asia; Sexual minorities -- Caribbean Area; Sexual health -- Developing countries; Reproductive health -- Developing countries; Reproductive health services -- Developing countries; Communication in reproductive health -- Developing countries; Sexual minorities -- Youth -- Developing countries; Medical policy -- Developing countries; Homophobia -- Developing countries